Jesus before the Gospels : how the earliest Christians remembered, changed, and invented their stories of the Savior - Ehrman, Bart D. (New York, NY : HarperOne, an imprint of HarperCollins Publishers, 2016)
Many believe that the Gospel stories of Jesus are based on eyewitness testimony and are therefore historically reliable. Now, for the first time, a scholar of the New Testament, New York Times bestselling author Bart D. Ehrman (Misquoting Jesus; and Jesus, Interrupted), surveys research from the fields of psychology, anthropology, and sociology to explore how oral traditions and group memories really work and questions how reliable the Gospels can be. Focusing on the decades-long gap between when Jesus lived and when these documents about him began to appear, Ehrman looks to these varied disciplines to see what they can tell us about how the New Testament developed.
Oral traditions and oral inventions -- The history of invention -- Eyewitness testimonies and our surviving gospels -- Distorted memories and the death of Jesus -- Distorted memories and the life of Jesus -- Collective memory : our earliest Gospel of Mark -- The kaleidoscopic memories of Jesus : John, Thomas, and a range of others -- A paean to memory.
Includes bibliographical references (pages [301]-315) and index.
Keywords: Jesus Christ -- Historicity; Jesus Christ -- Biography -- Sources